Pengaruh Visual Branding dan Engagement Instagram Terhadap Minat Mahasiswa Menggunakan Jasa Fotografi Wisuda di Kota Makassar - Nita Nurhalifah; Alem Febri Sonni; Muhammad Akbar (Jurnal Noken: Ilmu-Ilmu Sosial, 2026)
This study examines the application of visual branding and Instagram engagement by graduation photography service providers and their possible association with students’ interest in using these services. The rise of social media, particularly Instagram, has made visual elements and digital interaction important in shaping consumer perceptions, including those of students. This research adopts an exploratory quantitative approach using Structural Equation Modeling–Partial Least Squares (SEM-PLS) on data from 100 student respondents who are active Instagram users in Makassar. The evaluation of the measurement model shows that the adapted instrument did not meet the required reliability and convergent validity thresholds: Cronbach’s Alpha, Composite Reliability, and Average Variance Extracted (AVE) fell below the recommended cut-offs, with some negative values. Consequently, the resulting structural path coefficients are preliminary (exploratory) and cannot be interpreted as significant effects. The main contribution of this study is methodological: the instruments measuring visual branding and engagement in the context of Makassar students require refinement, partly due to limited response variation (ceiling effect) and sample size. This study provides a basis for refining the instrument and collecting further data before conclusive causal testing can be conducted.